Association between individual, household, and area-level socioeconomic status indicators and sensorineural hearing loss in adults in southwest Iran: a population-based study - Rahimi, Zahra; Saki, Nader; Cheraghian, Bahman; Amini, Payam; Solaymani Dodaran, Masoud (Frontiers in Public Health, 2023)
Introduction: Hearing loss is the fourth most common chronic disease, but studies on the relationship between hearing loss and socioeconomic factors are limited. We aimed to examine the association between hearing loss and socioeconomic factors among 35-70 year adults in southwest Iran. Methods: This population-based case-control study was conducted in the Hoveyzeh cohort study in adults aged 35-70 in southwest Iran between 2017 and 2021. Information on socioeconomic factors, demographic characteristics, comorbidities, family history of hearing loss, and noise exposure was collected. We assessed the relationship between three levels of socioeconomic factors (individual, household, and area level) with sensorineural hearing loss (SNHL). Multiple logistic regression was used to adjust the potential confounders. Results: Among a total of 1365 assessed participants, 485 patients were diagnosed as having hearing loss, and the other 880 individuals were diagnosed without hearing loss, which is considered the case and the control group, respectively. At the individual level of socioeconomic, the odds of having hearing loss in the participants with high school education and diploma, [OR=0.51(95%CI:0.28-0.92)], and the individuals with university education [OR=0.44(95%CI:0.22-0.87)] were significantly lower than the illiterate participants. At the household socioeconomic level, The odds of having hearing loss were lower for those with poor [OR=0.63(95%CI:0.41-0.97)] and moderate [OR=0.62 (95%CI:0.41-0.94)] wealth status versus those with the poorest wealth status. In the area level socioeconomic, although the odds of hearing loss in the residents of affluent areas were slightly lower than the residents of deprived areas, there was no significant difference among the groups. Conclusion: The individuals with hearing loss may have insufficient education and income.